PENGARUH SELF ESTEEM TERHADAP AKTIVITAS BELAJAR KELAS XI IPS DI SMA SANTO FRANSISKUS ASISI PONTIANAK - Julia, Yosie (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aim to know the effect of Self Esteem toward students learning activity ofXIIPSgrade on economic subject in SMA Santo Fransiskus Asisi the school year 2016/2017. This Method use descriptive quantitative design with correlational reseacrh form. the total of popultionare 150 students with the total of sampel are 60 student which determined by slovin formula, .Data taken by interect communication (questionnaire). Prerequisite test in this research is validity test and reliability test. Based on data analyze with simple linear regression is 9,181 which refer about the effect of independent variable towards dependent variable. The result of t-testis 9,181>2,002, so Ha accepted and Ho rejecedt, based on simple linear regretion get a formula Y = 6,393 + 0,585x. determination coefisien showedthe contribution of self esteem toward students learning activity is 59,2%.it showed self estem give significant effect toward students learning activity of XI IPS grade on economic subject in SMA Santo Fransiskus Asisi the school year 2016/2017.Keyword : Self Esteem, Learning Activity, Economy